Managing Institutional Diversity in Integrated Care: A Systematic Literature Review of Institutional Logics and Management Strategies - Marco Roth (International Journal of Integrated Care)
Introduction: This review examines the institutional diversity in integrated care due to various institutional logics and explores the essential management strategies for navigating this diversity effectively. Methods: This systematic literature review involved a comprehensive search across Scopus, Medline and Google Scholar. This process identified 1747 articles, with rigorous screening narrowing them down to eight key articles. Results: The study unveils five primary institutional logics in integrated care, focusing on their unique characteristics and how they interrelate, and highlights crucial management strategies for maintaining a balance among these diverse logics. Discussion: Applying the institutional logic perspective, this study uncovers the complex interplay of diverse logics shaping integrated care—a previously underexamined facet. Examining the foundational beliefs underlying organizational behaviour offers deeper insights into institutional complexities often overlooked in previous literature. This highlights the necessity for effective management strategies to reconcile conflicting logics, promoting more sustainable integrated care solutions. Conclusion: The review comprehensively explores institutional logics in integrated care, emphasizing the importance of holistic management strategies. It highlights the imperative for policymakers and healthcare administrators to balance operational efficiency, patient-focused care, and professional independence—essential elements in crafting successful integrated care frameworks.